Novel micromorphological features of wood and bark of Argentinean Simaroubaceae - Campagna, Maria Noel (2017)
Simaroubaceae is a family of about 22 genera and 100 species of mainly tropical and subtropical trees and shrubs and it is generally considered to be a heterogeneous group. In Argentina, Simaroubaceae is represented by three genera and four species, one of these is exotic: Ailanthus altissima (Mill.) Swingle while the other three are native: Castela coccinea Griseb., C. tweedii Planch. and Picrasma crenata (Vell.) Engl. Wood and bark anatomies of the Argentinean species were studied in an effort to find distinctive features for the genera and species within this family. Transverse, tangential and radial sections of the specimens were prepared and macerated according to conventional techniques; microscopic examination was performed by light microscopy and scanning electron microscopy. It was possible to make a key for the species and genera using a combination of qualitative (presence/absence of wood growth rings, porosity, abundance of parenchyma, occurrence of crystals, etc.), and quantitative features (vessels per square millimetre, tangential diameter of vessel lumina, etc.). The wood and bark characteristics obtained provide new evidence of the heterogeneous nature of the family. From an ecological point of view, according to vessel size, vessel number, mesomorphy and vulnerability index, the wood of the studied species belonging to Castela genus were characterised as xeromorphic, while the other genera were characterised as mesomorphic.